Concentrations and isomer profiles of hexabromocyclododecanes (HBCDDs) in floor, elevated surface, and outdoor dust samples from Basrah, Iraq. Issue 6 (6th June 2022) - Al-Omran, Layla Salih; Stubbings, William A.; Harrad, Stuart
Abstract : Within-room (between elevated surface dust and floor dust) and within-home (between indoor and outdoor dust) spatial variability in concentrations of HBCDDs were observed. Abstract : Concentrations of the α, β, and γ- diastereomers of hexabromocyclododecane (α-, β-, and γ-HBCDD) were measured in 60 dust samples from 20 homes across Basrah, Iraq. From each home, two indoor dust (ID) samples (specifically one collected from elevated surfaces (ESD) and one from the floor (FD)) were collected from the living room, with one outdoor dust (OD) sample collected from the front yard of the house. Concentrations of HBCDDs decreased in the following sequence ESD > FD > OD. For ID, ΣHBCDD concentrations varied from 5.3 ng g −1 in FD to 150 ng g −1 in ESD, with median levels of 60 and 40 ng g −1 in ESD and FD respectively. Concentrations of γ-HBCDD, and consequently of ΣHBCDDs in ESD, significantly ( p < 0.05) exceeded those in FD. For adults, this implies that exposure assessments based on FD only may underestimate exposure, as adults are more likely to ingest ESD. Concentrations of ΣHBCDDs in OD ranged between 7.4 and 120 ng g −1 with a median of 35 ng g −1 and were significantly exceeded ( p < 0.05) by those in ID samples. Concentrations of ΣHBCDDs in OD from houses with car parking areas exceeded ( p < 0.05) those in OD from other homes, implying vehicles as potential emission sources of HBCDDs. Simultaneously, there was moderate correlation ( R = 0.510–0.609, p < 0.05) between concentrations in ID and OD, implying that the indoor environment is an important source of OD contamination. The isomer pattern of HBCDDs in dust samples displayed a predominance of α-HBCDD, which represented 56%, 52% and 59% ΣHBCDD in ESD, FD and OD samples respectively. Derived from the concentrations reported in this study, the median and 95 th percentile estimated daily intakes (EDI) for Iraqi adults and toddlers through house dust ingestion did not exceed the reference dose (RfD) value for HBCDD.